2021
DOI: 10.3390/ijms222011138
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Salicylates in Willow Bark (Salix Cortex) for Targeting Peripheral Inflammation

Abstract: Salix cortex-containing medicine is used against pain conditions, fever, headaches, and inflammation, which are partly mediated via arachidonic acid-derived prostaglandins (PGs). We used an activity-guided fractionation strategy, followed by structure elucidation experiments using LC-MS/MS, CD-spectroscopy, and 1D/2D NMR techniques, to identify the compounds relevant for the inhibition of PGE2 release from activated human peripheral blood mononuclear cells. Subsequent compound purification by means of preparat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…One interesting option for future studies is the tannins, which are likely to be found in the willow bark water extracts and have recently been associated with antiviral efficacies (e.g., Vilhelmova-Ilieva et al, 2019 ; Fraga-Corral et al, 2021 ). Contradictory results and hypotheses exist on whether polyphenols influence the overall bioactive efficacy of willow extracts ( Khayyal et al, 2005 ; Nahrstedt et al, 2007 ; Antoniadou et al, 2021 ). Therefore, more research is needed to achieve any certainty regarding their effects on the bioactivities of willow extracts.…”
Section: Discussionmentioning
confidence: 99%
“…One interesting option for future studies is the tannins, which are likely to be found in the willow bark water extracts and have recently been associated with antiviral efficacies (e.g., Vilhelmova-Ilieva et al, 2019 ; Fraga-Corral et al, 2021 ). Contradictory results and hypotheses exist on whether polyphenols influence the overall bioactive efficacy of willow extracts ( Khayyal et al, 2005 ; Nahrstedt et al, 2007 ; Antoniadou et al, 2021 ). Therefore, more research is needed to achieve any certainty regarding their effects on the bioactivities of willow extracts.…”
Section: Discussionmentioning
confidence: 99%
“…After quantification of the PGE2 release, as described in section 4.11, it could be shown that fractions F5 and F6 were the most potent among the analyzed fractions. However, F5 had the highest statistical significance of p < 0.05 (Figure 19, Antoniadou et al (2021)). Moreover, COX-1 and COX-2 enzyme inhibitory activity was evaluated between fractions F4, F5, and F6 in order to examine any phytochemical carryover (Antoniadou et al 2021).…”
Section: Spe Fractionmentioning
confidence: 99%
“…The isolation and synthesis of salicin from willow bark in the form of aspirin in the late 1800s have been showing a significant role in pain relief. Willow bark's antiinflammatory and analgesic effects concern with salicin content which is a natural salicylic acid precursor 53 .…”
Section: Willow Barkmentioning
confidence: 99%